Resilience as a Process in Parents with Leukaemia Children: A Phenomenological Study - Utami, Agnes Sinta Dewi Tyas; Hanami, Yuliana (Analitika: Jurnal Magister Psikologi UMA, 2024)
Pediatric leukemia affects caregivers, including parents and siblings. When facing diagnosis and treatment, parents of patients face new adaptations such as financial, time and physical health issues. Resilience is one of the factors that influence the adaptation process. This study explores the experiences, reflections and personal meanings of parents related to the experience of accompanying children from cancer diagnosis to treatment and the resilience process experienced, including how coping strategies and social support play a role in the process of parents surviving in stressful situations due to accompanying childhood leukemia patients. This research uses a qualitative research method with a phenomenological approach. The data analysis used thematic analysis by collecting themes obtained from the results of the data collection process. Participants in this study were parents of leukemia patients who were at a Cancer Foundation in Bandung. The results of this study explain the dynamics of both negative and positive emotions, social support, problem-solving strategies and personal growth. Resilience is interpreted by overcoming negative emotions with social support that raises optimism as a positive emotion. Optimism becomes a motivation to do problem solving through problem focused and emotional focused. Through this process, caregivers interpret personal changes in individuals